Inclusión financiera en Bolivia: Un estudio de caso para los productores quinueros del Altiplano Sur - Adriana Beatriz Caballero Caballero (Institute for Advanced Development Studies (INESAD), 2024)
– This paper analyzes financial inclusion in Bolivia through aggregate indicators of access, and develops a case study for quinoa producers in the Southern Altiplano. Using primary data from a survey conducted by INESAD, it evaluates the factors that affect the probability of quinoa producers having a savings account in a financial institution. In other words, financial inclusion is addressed within a demand perspective, understood as access to savings services. Considering three categories of variables -socioeconomic, educational and connectivity-, the results reveal that the holding of a formal account among quinoa producers largely depends on their level of education and their access to information and communication technologies through a mobile phone or computer. Financial education shows a positive incidence, but significantly more important for producers who are part of the Fair Trade production scheme. In terms of employment status, individuals who generate income are more likely to be included in the financial system. On the other hand, gender is not a significant factor on its owm; however, when interacting with school dropout, it is found that women with incomplete schooling are a vulnerable group to financial exclusion. Finally, proximity to branches or agencies is not a significant factor; however, road structure is: greater distance to a highway has a negative impact on the financial inclusion of quinoa producers in the Southern Altiplano of Bolivia.
Keywords: E21; G51; O12; O13; Q1; 330; Household saving; financial instruments; financial inclusion; agricultural households; financial education